2012
DOI: 10.1508/cytologia.77.465
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Light-Dependent Cell Morphology and an Accumulation Response in <i>Ochromonas danica</i>

Abstract: Summary Recently, we discovered the LOV-containing blue light (BL) receptor, aureochrome, in the stramenopile alga Vaucheria. Aureochrome has been isolated in other stramenopile algae, such as Fucus and Ochromonas. The functional role of aureochrome has still not been identified in Fucus and Ochromonas. What kind of response does aureochrome mediate? Here, we investigated various light responses, such as cell morphology, motility and behavior in Ochromonas danica, by measuring cell dimensions and observing swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Therefore, physiological responses to environmental cues might represent a much better accessible phenotype for cells with altered aureochrome contents. Ishikawa et al (2012), for instance, observed that cell size and motility is blue-light (BL)-sensitive in the chrom-alveolate alga Ochromonas danica, but they also stated that this observation cannot be solely attributed to the function of aureochromes. Therefore, simple BL on/off experiments appear not to be promising for aureochrome characterization, considering that diatoms contain a large number of additional BL receptors belonging to the group of cryptochromes (see König et al, 2017), which may interfere with the aureochromes.…”
Section: The Physiological Function Of Aureochromes In Diatomsmentioning
confidence: 99%
“…Therefore, physiological responses to environmental cues might represent a much better accessible phenotype for cells with altered aureochrome contents. Ishikawa et al (2012), for instance, observed that cell size and motility is blue-light (BL)-sensitive in the chrom-alveolate alga Ochromonas danica, but they also stated that this observation cannot be solely attributed to the function of aureochromes. Therefore, simple BL on/off experiments appear not to be promising for aureochrome characterization, considering that diatoms contain a large number of additional BL receptors belonging to the group of cryptochromes (see König et al, 2017), which may interfere with the aureochromes.…”
Section: The Physiological Function Of Aureochromes In Diatomsmentioning
confidence: 99%
“…Moreover, light signals are also highly effective in controlling cyst germination, cell survival and accumulation, and cellular division in H. akashiwo (Doran and Cattolico, 1997;Lee et al, 2012;Shikata et al, 2007). In other stramenopiles algae such as diatoms, xanthophytes, and phaeophytes, BL also promotes germination of resting cells, modifies their growth and behavior, and controls their cell division (Huysman et al, 2010;Ishikawa et al, 2012;Kataoka, 1990;Kropf, 1992;Mercado et al, 2004;Shikata et al, 2009Shikata et al, , 2015Takahashi et al, 2001). The molecular mechanism responsible for the lightdriven process in these algae is less understood, however.…”
Section: Introductionmentioning
confidence: 99%